The Influence of Digital Marketing, Menu Diversity, and Service Quality on Customer Loyalty - Ufi Rumefi; Agus Andi Subroto; Jihad Agil Maulana Kusuma (Jurnal Indonesia Sosial Teknologi, 2025)
The background of this research is based on the increasingly competitive culinary business landscape in the digital era, where digital marketing strategies, menu variations, and customer service play a crucial role in maintaining customer loyalty. This research aims to test and analyze the influence of digital marketing, menu diversity, and service quality on customer loyalty among "Mie Mbah Joyo" consumers, who have a population of 64. This research employs a quantitative method with a survey approach. The sampling technique used a purposive sampling formula to determine a sample of 44 respondents. The results of the study indicate that these variables have a simultaneous influence. However, only two variables, digital marketing, and menu diversity, significantly influence customer loyalty. Of all the significant variables, the menu diversity variable has the greatest influence or is the most dominant on customer loyalty, with a value of 0.478. This study concludes that digital marketing strategies and attractive menu variations are more effective in increasing customer loyalty than service quality factors. The implications of this research highlight the importance of innovation in digital marketing and menu development to enhance the competitiveness of culinary businesses.